2001
DOI: 10.1046/j.1365-2583.2001.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of DNA sequence variation in chromosomally recognized taxa of Anopheles gambiae: evidence from rDNA and single‐copy loci

Abstract: Patterns of DNA sequence variation in the ribosomal DNA (rDNA) second internal transcribed spacer (ITS2) and five unlinked single-copy nuclear loci were examined for evidence of reproductive isolation among four chromosomally recognized taxa of Anopheles gambiae from West Africa: Savanna, Bamako, Mopti and Forest, as well as sibling species An. arabiensis and An. merus. Included among the single-copy loci were three sequence-tagged random amplified polymorphic DNA (RAPD) loci, two of which (R15 and R37) had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…The other loci (including the rDNA) are at the proximal (centromeric) end of the X chromosome Lehmann et al 2003). However, little differentiation has been found at loci elsewhere in the genome (Gentile et al 2001;Mukabayire et al 2001;Wang et al 2001;Turner et al 2005). Debate is ongoing as to whether such generally limited differentiation primarily reflects insufficient time for differentiation to have occurred or ongoing introgression among forms.…”
Section: Discussionmentioning
confidence: 99%
“…The other loci (including the rDNA) are at the proximal (centromeric) end of the X chromosome Lehmann et al 2003). However, little differentiation has been found at loci elsewhere in the genome (Gentile et al 2001;Mukabayire et al 2001;Wang et al 2001;Turner et al 2005). Debate is ongoing as to whether such generally limited differentiation primarily reflects insufficient time for differentiation to have occurred or ongoing introgression among forms.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the taxonomic status of these chromosomal forms is still debated (Black and Lanzaro, 2001). In an extensive study addressing this problem, Mukabayire et al (2001) suggested that neutral markers may not have the sensitivity required to detect isolation between recently established taxa. If this is true, then the Tinh Quang population might be much more isolated than we estimated.…”
Section: Discussionmentioning
confidence: 99%
“…A. gambiae (sensu strictu) has been distinguished into several different ecotypes on the basis of floating chromosomal inversions, whose prevalence varies geographically and seasonally, suggesting that they may ''lock in'' specific allelic combinations important for malaria transmission (35,36). More recently, a small number of molecular markers have also suggested the existence of flexibility and even mosaicism in the A. gambiae genome (37,38). The high level of polymorphism that we detected between BAC 8N20 and the Consensus Sequence is reminiscent of the human MHC locus, which encompasses at least 200 genes, most of which are highly polymorphic and have roles in immune responses (39).…”
Section: Discussionmentioning
confidence: 99%